Digital Media Integration in Cultural Arts Learning: A Case Study of a Digital Madrasah in Indonesia - Mirna Rasuani; Tri Widayatsih; Yessi Fitriani (Yayasan Sembilan Pemuda Indonesia, 2026)
This qualitative study explores the integration of digital media in Cultural Arts learning at MAN 3 Palembang, a designated digital madrasah in Indonesia. Through observations, interviews, and document analysis involving 29 students and teachers, the research examines how tools like Canva, CapCut, and Quizizz enhance student creativity, engagement, and learning outcomes. Findings reveal that while digital tools foster motivation and collaboration, challenges such as internet access and digital literacy gaps persist. The novelty of this research lies in its exploration of digital transformation within an Islamic educational context, emphasizing the integration of technology with cultural and artistic values. Practically, the findings provide a model for implementing digital learning in art-based subjects that align with the vision of Madrasah Smart Digital. The study contributes to the TPACK and SAMR frameworks by demonstrating their applicability in Islamic arts education, offering a model for technology integration in culturally responsive pedagogy.